THE VIEWS OF THE SOCIAL STUDIES TEACHERS ON DEVELOPING STUDENTS’ SELF-CONTROL SKILLS - Aksüt, Selda (My University, 2020)
The study aimed at determining the views of the Social Studies teachers on developingtheir students’ self-control skills. This study was conducted with the phenomenologicaldesign, one of the qualitative research designs. The participants of the study was composed of25 Social Studies teachers in eight secondary schools in city center of Elazığ, Turkey duringSpring Semester of 2019-2020 school year. The participants were determined viaconvenience sampling model, which is one of the purposeful sampling methods. The data ofthe study were obtained using the interview technique via semi-structured interview forms. Inthe analysis of the data content analysis method was utilized. As a result of the study, it wasdetermined that Social Studies teachers defined self-control skills as the capacity to controland check themselves. Self-control skills were determined to have positive contributions onlearning in Social Studies teaching such as skills development, awareness of responsibilities,and being independent and self-confident. Families and teachers can be ensured to be modelsfor students in order to develop and develop self-control skills. In developing self-controlskills, different methods and techniques can be included in the teaching process consideringthe individual differences and developmental levels of students.
Keywords: Eğitim; Eğitim Araştırmaları; Psikoloji